Z Konstantynopola do Rzymu. Ilustrowane przepowiednie w służbie średniowieczne] propagandy politycznej i religijnej - Potesta, Gian Luca (Poznańskie Studia Teologiczne, 2009)
The paper was presented in Poznań on 23 April 2009 during an open seminar dedicated to a phenomenon of prophetism in the Middle Ages. The subject of the lecture is medieval pope prophecies Genus nequam, their genesis, their rhetoric and conversions which they underwent in the Middle ages. The archetype of prophecies Genus nequam well-known in the West were Byzantine Oracula Leonis. They belong to the so-called basileiographeion, i.e. medieval pamphlets, directed against ruling Byzantine emperors. The motive of a she-bear and an emperor rising from the dead in Oracula Leonis gave inspiration to obscure authors of Genus nequam. The she-bear was associated with the pope Nicholas III, coming from a powerful Roman family Orsini and famous for his nepotism. The resurrected emperor from Oracula Leonis served as an example of an ideal pope who would reform church. A negative character of a man with a sickle and a rose noticeable in Byzantine prophecies was modified so as to point to the pope Celestine V (1294). Circles of radical supporters of church reform were glad of his appointment and hoped for renewal. After his rapid resignation the prophecies started announcing another pope, who would continue the interrupted mission of Celestine V. Genus nequam are the example of an interesting medieval collection of symbols and figures, which may convey specific religious and political information.